Improving Service Quality Through the Performance of State Civil Apparatus in Sangir Batanghari District - Mesra, Meslidar; Hariadi, Berian (Adabi : Journal of Public Administration and Business, 2023)
The purpose of this research is to find out and describe the performance of state civil servants in improving the quality of service in Sangir Batang Hari District and to find out the supporting and inhibiting factors for the performance of state civil servants in improving service quality in Sangir Batang Hari District. This type of research is qualitative descriptive research. The results of the research show that the performance of state civil servants in improving the quality of services in Sangir Batang Hari District still needs to be improved. Progress in carrying out the work of the state civil apparatus can be seen from the use of technology-based systems. This can make it easier and shorten the time in carrying out services to the community. However, there are still several things that need to be improved in improving the quality of bureaucracy in Sangir Batang Hari District. As an example of an attitude of initiative, smiling and being friendly towards the community which must be further improved by the state civil servants. There is a need to increase the dissemination of information to the public, because so far there are still many people who do not understand the rules of administrative affairs, considering that a lot of time is wasted when people come without bringing complete requirements. Apart from that, it is necessary to complete and improve inadequate facilities and infrastructure, for example the number of computers, work space equipment and waiting rooms. Because if the facilities and infrastructure are inadequate, this will certainly affect the quality of service.